Temperature influences the reproduction of fiddler crabs at the southern edge of their distribution - Delevati Colpo, Karine (2017)
Understanding the spatial patterns of reproductive biology might provide predictions about fitness and population stability in different locations within the geographical range of a particular species. Leptuca uruguayensis is a fiddler crab that breeds year round in tropical estuaries but only in summer months in temperate salt marshes. In this study, we examined several reproductive attributes of the southernmost population of L. uruguayensis, including the proportion of ovigerous females, the proportion of surface-active crabs, the developmental status of the gonads and hepatopancreas, and the fullness of seminal receptacles, and related them to environmental factors such as temperature, photoperiod, and sediment organic matter content. We found that temperature was the environmental factor that was most correlated with the reproductive process of the southernmost fiddler crab, since this environmental factor was related to ovarian development, to the fullness of seminal receptacles, and to the hepatosomatic index. At the southern edge of its distribution, the low temperatures of winter restricted reproduction in L. uruguayensis. These winter temperatures might represent the lower limit of the thermal window of this fiddler crab, limiting its extension toward higher latitudes.